Trust in Government and Fiscal Adjustments - Dirk Bursian; Alfons Weichenrieder; Jochen Zimmer (Center for Economic Studies and ifo Institute (CESifo), 2013)
The paper looks at the determinants of fiscal adjustments as reflected in the primary surplus of countries. Our conjecture is that governments will usually find it more attractive to pursue fiscal adjustments in a situation of relatively high growth, but based on a simple stylized model of government behavior the expectation is that mainly high trust governments will be in a position to defer consolidation to years with higher growth. Overall, our analysis of a panel of European countries provides support for this expectation. The difference in fiscal policies depending on government trust levels may help explaining why better governed countries have been found to have less severe business cycles. It suggests that trust and credibility play an important role not only in monetary policy, but also in fiscal policy.
Keywords: H62; E62; 330; trust; debt sustainability; fiscal reaction function; euro area; EU